2009
DOI: 10.1021/jp904232n
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Mechanisms for the Gas-Phase Unimolecular Decomposition of DMMP

Abstract: All species involved in the multichannel decomposition of gas-phase dimethyl methylphosphonate (DMMP) were investigated by electronic structure calculations. Geometries for stationary structures along the reaction paths, were fully optimized with the MP2 method and the B3LYP and MPW1K DFT functionals, and the 6-31G*, 6-31++G**, and aug-cc-pVDZ basis sets. The geometries determined by the B3LYP and MPW1K functionals are in very good agreement with the MP2 values. Increasing the basis set size from 6-31G* to aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 46 publications
2
44
1
Order By: Relevance
“…1 and the Supplementary Discussion. We observed good agreement between our computed values and previously obtained experimental13 and computed14 values.…”
Section: Resultssupporting
confidence: 89%
“…1 and the Supplementary Discussion. We observed good agreement between our computed values and previously obtained experimental13 and computed14 values.…”
Section: Resultssupporting
confidence: 89%
“…22 Note that this mechanism is only possible for gas-phase reactions; in the solution state this is not a feasible degradation pathway. 1,3 In combination with earlier studies, 23 the results for unimolecular decomposition showed that the 6-membered-ring TS is energetically favoured with a second most stable TS somewhere over 100 kJ mol À1 higher on the potential energy surface (PES). The structure of VX allows such calculations to be carried out on both the ester and thioester side chains.…”
Section: Introductionsupporting
confidence: 54%
“…Comparison with literature showed significant discrepancies especially for reactions involving P-O bonds and highlighted the fact that reaction rates based on analogous C-O bond chemistry are unreliable. More recently, a theoretical investigation of unimolecular decomposition of DMMP was reported by Yang et al [21]. The most favourable elimination through a 4-membered transition state yields methanol and O=P(CH 2 )(OCH 3 ) and involves a barrier of 73.2 kcal mol -1 at the CBS-QB3 level of theory.…”
Section: Introductionmentioning
confidence: 99%